2018
DOI: 10.1063/1.5037185
|View full text |Cite
|
Sign up to set email alerts
|

Antiferroelectricity in lanthanum doped zirconia without metallic capping layers and post-deposition/-metallization anneals

Abstract: We report the effects of lanthanum doping/alloying on antiferroelectric (AFE) properties of ZrO2. Starting with pure ZrO2, an increase in La doping leads to the narrowing of the AFE double hysteresis loops and an increase in the critical voltage/electric field for AFE → ferroelectric transition. At higher La contents, the polarization-voltage characteristics of doped/alloyed ZrO2 resemble that of a non-linear dielectric without any discernible AFE-type hysteresis. X-ray diffraction based analysis indicates tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Our theory of depolarization-induced nucleation inhibition is thus an excellent corollary to thin films that do not exhibit Kolmogorov–Avrami–Ishibashi switching but nucleation limited switching or inhomogeneous field switching. , We therefore allow the condition that the observed coercive field in a first-order ferroelectric can increase until the total field in the ferroelectric, when summed with the switching-induced depolarization field, is smaller than the back-switching field. Such depolarization-induced nucleation inhibition can further explain the shift of the observed coercive field in ZrO 2 antiferroelectrics. , …”
Section: Modeling Ferroelectric Hysteresismentioning
confidence: 89%
See 1 more Smart Citation
“…Our theory of depolarization-induced nucleation inhibition is thus an excellent corollary to thin films that do not exhibit Kolmogorov–Avrami–Ishibashi switching but nucleation limited switching or inhomogeneous field switching. , We therefore allow the condition that the observed coercive field in a first-order ferroelectric can increase until the total field in the ferroelectric, when summed with the switching-induced depolarization field, is smaller than the back-switching field. Such depolarization-induced nucleation inhibition can further explain the shift of the observed coercive field in ZrO 2 antiferroelectrics. , …”
Section: Modeling Ferroelectric Hysteresismentioning
confidence: 89%
“…Such depolarization-induced nucleation inhibition can further explain the shift of the observed coercive field in ZrO 2 antiferroelectrics. 21,51 2.4. Ferroelectric Hysteresis with Depolarization.…”
Section: Modeling Ferroelectric Hysteresismentioning
confidence: 99%
“…[3,13] Antiferroelectric ZrO 2 thin (≈10 nm) films can be obtained through post-deposition or post-metallization annealing in N 2 atmosphere, [13] or by employing higher temperatures during atomic layer deposition (ALD) of the heterostructures. [14] The key to obtaining antiferroelectric responses therein (as opposed to paraelectricity or ferroelectricity) is to stabilize the tetragonal phase (space group P4 2 /nmc), [6,15] while partially or completely suppressing the bulk monoclinic phase (space group P2 1 /c) and other polymorphs. [6,16] Theoretical studies have suggested that the fieldinduced polar phase in ZrO 2 is an orthorhombic one, [6,17] similar to the polar phase found in HfO 2 -based ferroelectrics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, r P is larger for La-doped compared with that of Al-doped HfO 2 NPs. There are some differences in the electric properties of ion doped HfO 2 and ZrO 2 nanostructures [43] [45] [46]. For example Yoo et al [43] observed that the dielectric constant in Al doped HfO 2 thin films undergoes a maximum whereas in Al doped ZrO 2 thin films it decreases.…”
Section: Discussionmentioning
confidence: 99%